Evaluasi Implementasi Sistem Pertolongan Kecelakaan Penerbangan dan Pemadam Kebakaran (PKP-PK) dalam Mendukung Penanganan Darurat Penerbangan di Bandar Udara - Kristian Omren Rumahorbo; Bravolta Sembiring; Nawang Kalbuana (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2026)
Previous research or relevant studies play an important role in strengthening theory and explaining the relationships between variables in scientific research. This article reviews the factors that influence aviation emergency handling at airports, namely the readiness of PKP-PK personnel, PKP-PK facilities and infrastructure, as well as response time and PKP-PK emergency management system. The purpose of writing this article is to build hypotheses regarding the influence between variables that can be used in subsequent research. The research method used is a qualitative method with a literature review approach through the collection and analysis of relevant national and international journals related to the implementation of the Aircraft Accident and Fire Fighting Assistance (PKP-PK) system. The results of this literature review article are: 1) the readiness of PKP-PK personnel influences aviation emergency handling at airports; 2) PKP-PK facilities and infrastructure influence aviation emergency handling at airports; and 3) response time and PKP-PK emergency management system influence aviation emergency handling at airports.